Effects of ammonia on shrimp physiology and immunity: a review - Mingming Zhao; Defu Yao; Shengkang Li; Yueling Zhang; Jude Juventus Aweya (Reviews in Aquaculture, 2020)
The rapid expansion in shrimp farming comes with problems such as inadequate culture technology, disease outbreak, water pollution and other environmental degradation‐related problems. Prominent among these is the level of ammonia, which has been rising steadily in the last couple of years, mainly due to farming practices and other anthropogenic activities, and therefore has had consequent effects on marine life, especially shrimp. While optimal ammonia levels are a good source of nitrogen for marine phytoplankton that increases the level of dissolved oxygen in water as well serves as food for shrimp, high levels of ammonia are harmful to shrimp. When shrimp pond ammonia levels go beyond the tolerance limits, it inhibits chitinase expression, moulting, growth, phenoloxidase and haemolymph antimicrobial activity, thereby attenuating shrimp innate immune response. In this review, we bring together recent information on the effects of ammonia stress on the growth, physiology, biochemistry, ammonia‐metabolizing enzymes and immunity of shrimp. We also propose areas of research that can be explored in the breeding of new ammonia‐tolerant and disease‐resistant shrimp with robust immune and/or physiological systems that could withstand environmental stress and pathogens.